Wearable Robots Benchmarking: Comprehending and Considering User Experience - Beckerle, Philipp (Wearable Robotics: Challenges and Trends, 2022)
In real-world applications, wearable robots need to serve functional requirements, but also satisfy user demands. A systematic evaluation will require multidisciplinary benchmarking methods. Since user experience seems to be of distinct relevance, this paper analyzes how user experience influences wearable robots use and how it can be considered in benchmarking. Focus is set on potential metrics and how we could include them in human-centered benchmarking approaches.
CRIS-Team Scopus Importer:2021-09-24